HARTA BERSAMA SEBAGAI OBJEK JAMINAN DALAM PERJANJIAN KREDIT DIKAITKAN DENGAN KESETARAAN KEDUDUKAN SUAMI DAN ISTERI DALAM HUKUM PERKAWINAN - Sonny Dewi Judiasih (Indonesian Journal of Dialectics, 2011)
Matrimonial property has the economic value that can become a guarantee object for the credit contact, whereas the husband and wife bound in legal marriage have equal rights and obligations upon their matrimonial property. There was three identified problems as follows : (1)  is about the equal position between husband and wife based on principle of justice in credit contract which may lead to the liability in the settlement of their debt, (2) with regard to the legal certainty of their matrimonial property as a guarantee for their credit contract when a marriage was terminated, (3) a perspective of matrimonial property related to the development of national property law.This research applies juridical normative and descriptive analysis approaches. This research undertaken by library research and field research as the supporting data. For analysing data, it was used in normative qualitative method.The result of this research showed that, firstly, the equal of rights and duties between husband and wife on matrimonial property given the rights to conclude credit contract with matrimonial property as a gurantee object. Secondly, husband and wife that conclude credit contract with matrimonial property should fulfill for the payment of their debt as a legal certainly for creditors, no matter if the marriage was terminated. Thirdly, matrimonial property that is used as the guarantee object must be subjected as the unity property and as a part and parcel of their property as long as debts is paid.